2016
DOI: 10.4194/1303-2712-v16_3_04
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Artificial reproduction of common barbel (Barbus barbus) under controlled conditions usually did not exceed 10% of ovulation success. The aim of the study was to optimise the process of artificial reproduction of the barbel (cultured generation F4) with thermal and hormonal stimulation The first experiment examined the effect of stimulation with thermal conditions on the ovulation and the embryos survival rates. After the optimum conditions of thermal stimulation in barbel reproduction were determined, another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The embryo survival rate in this group was only slightly lower than the rate for embryos hatched from the eggs from Ovopel-injected females. A similar observation was made for common dace L. leuciscus [11,20], asp L. aspius [12], ruffe Gymnocephalus cernua [31], common barbel Barbus barbus [32], river lamprey Lampetra fluviatilis [34], European catfish S. glanis [46], ide L. idus [48,54] and burbot L. lota [55]. The present study clearly shows that Ovopel is the best reproduction stimulator for blue bream caught in the wild.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The embryo survival rate in this group was only slightly lower than the rate for embryos hatched from the eggs from Ovopel-injected females. A similar observation was made for common dace L. leuciscus [11,20], asp L. aspius [12], ruffe Gymnocephalus cernua [31], common barbel Barbus barbus [32], river lamprey Lampetra fluviatilis [34], European catfish S. glanis [46], ide L. idus [48,54] and burbot L. lota [55]. The present study clearly shows that Ovopel is the best reproduction stimulator for blue bream caught in the wild.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the possibility of its excretion by some females and the impact on other breeders in our experiment was imperceptible, as evidenced by the results from the control group (ovulation-0%). Determination of the optimal stimulation conditions, including simultaneous environmental conditions and hormonal agents, is necessary for the effective artificial reproduction of cyprinids [32]. The studies conducted thus far on cyprinids have shown that off-season breeding, although more difficult to carry out, requires the use of thermal conditions that are the same as those used in the season [11,13,14,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In every trail each species was divided into four groups. Outcomes were calculated after treatments of ovaprim hormone (Nowosad et al, 2016;Naeem et al, 2005). These results show that degree-hours directly affect the spawning response and…”
Section: Resultsmentioning
confidence: 99%